It's nothing personal, or is it? Exploring the competitive implications of relational multiplexity in supply chains. Issue 2 (24th March 2022) - Howe, Michael; Jin, Yao
Abstract: Supply chain relationships—both within and between firms—can have significant implications on the firm's ability to successfully compete. Thus, it is increasingly important for supply chain managers to skillfully navigate multiplex relationships to coordinate and manage resources across functions and firms in today's competitive environment. In this work, we describe, in a supply chain context, how the prevalence of multiplex relationships, which exist when multiple, potentially incongruous relationships are present between firms and among individuals within these firms, is an important basis for individual behaviors that influence firm competitiveness. Drawing on recent advances in the relational multiplexity theoretical perspective, we identify and discuss several research opportunities for enriching our understanding of interpersonal level antecedents of firm competitiveness. Specifically, we present research opportunities related to supply chain behavioral implications of individual differences and socio‐structural adaptation, informal relationship capitalization and creation, temporal orientation and transience, contemporary multiteam structures, and cross‐level relational valence (a)symmetries. Throughout, we emphasize the importance of the informal, interpersonal relationships that overlay formally specified roles and develop representative research questions to spur further exploration in each area.